(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The rapid digitalization of healthcare systems worldwide requires the transformation of medical education to develop students’ digital competencies. This article aims to improve the methodology of forming digital competencies among medical students by integrating innovative digital tools, blended learning strategies, and competency-based approaches. Using a mixed-methods research design, this study examines current challenges in digital competency formation and proposes an improved methodological framework for effective integration into medical curricula. The findings suggest that systematic use of simulation technologies, e-learning platforms, and interprofessional digital collaboration can significantly enhance students’ readiness for modern healthcare practice.